Socio-Theological Expression in the Sajen Tradition: A Study of the Javanese Community of Mawar Village, Langkat Regency - Muhammad Fikri Gemilang; Salahuddin Harahap; Ryandi (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to explore the tradition of sajen in Javanese society through the lens of social theology. The research problem focuses on how the community interprets sajen and how social theology can be applied to analyze this phenomenon. Employing a qualitative method with a field study approach in Mawar Village, Langkat Regency, data were collected through observation, interviews, and documentation. The findings reveal two primary dimensions of offering : first, as a spiritual expression related to the transcendent dimension of human existence; and second, as a social instrument that strengthens solidarity and cultural identity within the Javanese community. The continued practice of offering can therefore be understood not merely as a religious ritual but also as a manifestation of symbolic values expressed in the social sphere, which in turn reinforces communal cohesion and harmony.